Quality of care for abortion‐related complications: Insights from the WHO Multi‐Country Survey on Abortion‐related Morbidity across 11 African countries. (21st January 2022) - Kouanda, Seni; Qureshi, Zahida
Synopsis: A collection of seven papers from the WHO Multi‐Country Survey on Abortion‐related morbidity (MCS‐A) using secondary data analysis to assess the quality of care for abortion‐related complications in facilities in Sub‐Saharan Africa.